Penguatan Nilai-Nilai Profetik Masyarakat Desa Cisaat dalam Kegiatan Pendidikan Keagamaan Melalui Program Muslim Friendly Tourism - Muhamad Ridwan Effendi; Firdaus Wajdi; Izzatul Mardhiah; Sa’dullah Sa’dullah; Naila Fathiya Salsabila; Naila Aleea Joan (Muttaqien Publishing Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR. KH.EZ. Muttaqien Purwakarta, 2022)
Cisaat Village has been designated as an educational tourism village. This determination is based on the achievements of the Jakarta State University Community Service program, which has provided assistance to national-level tourist villages in 2020 for Cisaat Village as an educational tourism village from the Ministry of Tourism and the Creative Economy of the Republic of Indonesia. As an educational tourism village, Cisaat Village must be mapped and developed in various aspects of tourism, including religious tourism objects. Based on this, this community service activity for the Faculty Assisted Area (PKM-WBUF) program is to assist one of the Muslim Friendly Tourism development programs in the form of strengthening prophetic values ​​in religious education activities for the people of Cisaat Village, Ciater District, Subang Regency through activities counselling and mentoring of the Muslim Friendly Tourism (MFT) program. As a result, this activity has had a positive impact in the form of a growing understanding of the people of Cisaat Village as an educational tourism village on the concept of the Muslim Friendly Tourism (MFT) program. With awareness of this understanding, the community, especially the participants of the outreach activities, will follow up in the form of assistance to the Cisaat Village community.